Shifts of intercultural communicative competence experienced by international students - Rohani, Siti; Maulidiyah, Fitrotul; Dewi, Anita Sartika; Roshid, Mohammod Moninoor; Hariyanto, Sugeng (Universitas Ahmad Dahlan, 2025)
Intercultural communication is a vital component of modern education, necessitating efforts to enhance students’ Intercultural Communicative Competence (ICC). Achieving this requires intentional strategies, such as exposing students to international learning environments. Immersing students in international learning environments—such as through international programs or short-term overseas courses—can foster ICC development. Consequently, identifying shifts in ICC and effective strategies for its development is essential. This study was aimed at exploring the shift in ICC as experienced by international students as well as the intercultural communication problems encountered. This mixed method research was of explanatory-exploratory design with the respondents of Indonesian students taking a course in Singapore and foreign students pursuing a study in Indonesia. Data collection instruments used were questionnaires, focus group discussions, and in-depth interviews. Findings of the study reveal that students taking courses in other countries improved their ICC in all four categories in terms of knowledge, attitude, skills, and awareness. Problems encountered included linguistic, social, and cultural problems.